Epileptic phenotypes, electroclinical features and clinical characteristics in 17 children with anti-NMDAR encephalitis - Haberlandt, Edda; Plecko, Barbara; Schubert-Bast, Susanne (European journal of paediatric neurology, 2017)
Background: Anti-N-methyl d-aspartate receptor (NMDAR) encephalitis is a rare disorder characterized by seizures, neuropsychiatric symptoms, dyskinesia and autonomic instability. Objective: Aim of the present study was to evaluate the seizure phenotypes and electroencephalogram (EEG) features in children with anti-NMDAR encephalitis. Methods: Seizure types, electroclinical features and clinical characteristics of 17 children with anti-NMDAR encephalitis were analysed in a retrospective case series from nine centres in Europe. Results: Nearly half (8/17) of the children presented with psychiatric symptoms, whereas in 4/17 patients seizures were the first symptom and in 5/17 both symptoms occurred at the same time. During the following course seizures were reported in 16/17 children. The first EEG detected generalized slowing in 11/17 patients, focal slowing in 3/17 and normal background activity in only 3/17 children. The extreme delta brush (EDB) pattern was detected in 9/17 (53%) patients. Conclusion: In addition to psychiatric symptoms, children with anti-NMDAR encephalitis often show generalized slowing in EEG with or without seizures at initial presentation. EDB is present in half of all children and is potentially a helpful tool for early detection of this immune-mediated disease.